EDUKASI PENGURANGAN SAMPAH PLASTIK SEKALI PAKAI DI SDN 4 SIRNAJAYA TAROGONG KALER GARUT - Lubis, Novriyanti; Rutamsyah, Ardi (Universitas PGRI Yogyakarta, 2025)
The issue of waste accumulation has become one of the challenges and difficulties faced by every country in the world. This also applies to Indonesia, including the cities in this country. What draws special attention is the plastic waste produced, despite the many uses of plastic in human life. Plastic takes a very long time to decompose. The use of plastic in society has become a habit because it is more practical, including what is done by vendors at SDN 4 Sirnajaya, which is located in the Tarogong Kaler district of Garut Regency. Getting into the habit of reducing single-use plastic waste becomes a solution, especially for students, to understand and recognize the importance of reducing single-use plastic waste so that they can become individuals who can care for this earth. The PKM activity that has been carried out aims to emphasize the importance of education regarding the reduction of single-use plastic waste among the students of SDN 4 Sirnajaya. After the outreach, the students better understood the importance of maintaining environmental welfare and the significance of reducing waste. The outreach activities successfully increased students' awareness of the harmful effects of plastic waste, as shown by current data, and encouraged them to be more concerned about environmental cleanliness. Effective education, including the use of media such as animated videos, has proven to enhance students' understanding and enthusiasm for the material presented. Keywords: Student Education, Plastic Waste, Single-Use Plastic.